5x+6x-80=60-9x

Simple and best practice solution for 5x+6x-80=60-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+6x-80=60-9x equation:


Simplifying
5x + 6x + -80 = 60 + -9x

Reorder the terms:
-80 + 5x + 6x = 60 + -9x

Combine like terms: 5x + 6x = 11x
-80 + 11x = 60 + -9x

Solving
-80 + 11x = 60 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-80 + 11x + 9x = 60 + -9x + 9x

Combine like terms: 11x + 9x = 20x
-80 + 20x = 60 + -9x + 9x

Combine like terms: -9x + 9x = 0
-80 + 20x = 60 + 0
-80 + 20x = 60

Add '80' to each side of the equation.
-80 + 80 + 20x = 60 + 80

Combine like terms: -80 + 80 = 0
0 + 20x = 60 + 80
20x = 60 + 80

Combine like terms: 60 + 80 = 140
20x = 140

Divide each side by '20'.
x = 7

Simplifying
x = 7

See similar equations:

| 342x=1026 | | 3x-2=9x+4 | | 4y-48= | | 41y^2=33y | | 18u+5u^2=35 | | 3x+1=4+3x-3 | | -121=-4y^2 | | w+5+2(w+2)= | | 7x=3x+4x | | 8w=-6 | | 3/5x-1/42 | | w(10-3w)= | | 4/5-z=7 | | 2a-2+4=-2+a+a | | (-2x^2)+4x=-1 | | 2x^2+kx+3=0 | | 6(p-3)=15 | | 3x^2-2=31 | | 14+x=41 | | 4y=44yx | | -y/3=11 | | X(9)=72 | | 28xy=4y | | -(-4x+9-1)= | | (3x-7)+(5x+6)= | | 2x+7+x=4x+25 | | 36-9x=144+4x | | (6/7wz^7)(1/5w^2z^2) | | 72x^5+4-9x^2-32x^3= | | 6x+8+7x=151 | | 2w+w(w-10)=2w-19 | | 11w^2+39w=0 |

Equations solver categories